(untitled) (Revista científica Olimpia, 2019)
The World Organization of the Health (OMS), it classifies the obesity like the epidemic of the XXI century, and she notices that every time the number of obese people grows in the world. In Spain it is calculated that between the 40 and the population’s 45% he has overweight. In Cuba she is considered that around a 20 to 30% people are considered with overweight. It is a purely mathematical question: if we spend all the calories that we ingest, neither we put on weight neither we lose weight, if we consume less than what we ingest, we put on weight; but if we contribute less calories of those than we spend, we lose weight, it is for this reason that presently articulate a group of choreographies it is presented with aerobic exercises of under impact to diminish the corporal weight of the obese practitioners. For the design of this group of choreographies the following scientific methods were used: of the theoretical level the analysis and synthesis, the inductive-deductive one and the systemic one structural functional, those of the empiric level were also used the observation (not structured), pre experiment, the mensuration and in the statistical one the percentage calculation.